2018
DOI: 10.5424/sjar/2018162-12130
|View full text |Cite
|
Sign up to set email alerts
|

Valuation of nutritional and health claims for yoghurts in Spain: A hedonic price approach

Abstract: This article investigates price effects of nutritional claims (NC) and health claims (HC), in addition to other attributes, on yoghurts in the Spanish market. Prices and product characteristics are collected from yoghurt label references found on the shelves of the main representative retail shops in the capital city of Aragon (Zaragoza) Spain. The total sample included 508 yoghurts. Nutritional and health claims (NHCs) are selected based on the official definitions of the (EC) Regulation No 1924/2006 and No 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 46 publications
(51 reference statements)
1
21
0
Order By: Relevance
“…Overall, the results indicate that consumers positively value both NCs and HCs on yoghurt FOPs. This is consistent with the general literature review findings that consumers are willing to pay premium prices for these type of claims [15,17,20,26,27,61,62]. In addition, this result aligns with previous research, which suggests that individuals prefer dairy products with HCs and NCs rather than similar ones without these claims [18,63,64].…”
Section: Discussionsupporting
confidence: 91%
“…Overall, the results indicate that consumers positively value both NCs and HCs on yoghurt FOPs. This is consistent with the general literature review findings that consumers are willing to pay premium prices for these type of claims [15,17,20,26,27,61,62]. In addition, this result aligns with previous research, which suggests that individuals prefer dairy products with HCs and NCs rather than similar ones without these claims [18,63,64].…”
Section: Discussionsupporting
confidence: 91%
“…In addition, on breakfast biscuits consumers positively value the claims "high in fiber" and "reduced saturated fat" [15], likewise on cheese the valuation for the low saturated fat claim was higher than the valuation for the low fat claim [25]. On the contrary, a study using a hedonic prices approach found no market valuation for the nutritional claims related to fat, sugar and fiber in the case of yogurts [26]. In particular, they stated that market prices for food products with the nutritional claims "fat free", "no sugar", and "source of fiber" are not statistically different from food products without these claims.…”
Section: Discussionmentioning
confidence: 96%
“…HPM has been extensively used to analyze differentiated markets [31,32,33,34,35,36,37]. It has been used by environmental economists [38,39,40], in labor economics [41] and in agricultural economics [25,42,43,44,45]. No previous study has studied implicit prices for attributes of gluten-free food.…”
Section: Methodsmentioning
confidence: 99%